Analysis Effectiveness VOIP Over MPLS-IPVPN For State Government Network - Ismail, Mohd Hairul Shah (2017)
The performance of the Voice over IP (VoIP) protocol is of interest when planning for public access. The technologies, which work well for limited use often, fail to scale-up to the user requirements. High-quality VoIP services are required as for the Internet communications to be an alternative towards Public Switched Telephone Network (PSTN). The deployment of VoIP in the Internet network does not promise a good Quality of Service (QoS), since Internet is a kind of best-effort networks. The privacy consideration is also of importance when provisioning voice services on the Internet; particularly from the business use perspective. A full study, which comes up with a definitive set of recommendations would require considerable work over a substantial period of time, however some information on the performance may be obtained by reenacting the most commonly occurring conditions in the lab to ascertain the sensitivity of the VoIP to its key QoS parameters. The aim of this project is to analyze effective VOIP technique and analyze the performance of VoIP communications by observing the QoS parameters variation with respect to the some of the pertinent communication aspects on State Government Network. The aspect chosen in this regard comprise the call signaling protocols, the networking environments, and VPN protocols. Some similar studies have also been used as a comparative measurement towards the results obtained from this research.